Selection of Solid Wheel Train Procurement Vendors at PT Kereta Api Indonesia (Persero) in Bandung Using the Profile Matching Method - Muhammad Rafli*; Aditia Sovia; Saptono Saptono (Universitas Syiah Kuala, 2023)
PT Kereta Api Indonesia is a State-Owned Enterprise (BUMN) engaged in passenger and freight transportation services using trains. To improve the existing facilities and infrastructure at PT KAI, one of the factors in the procurement of goods and services that can support and support the running of train operations is the solid wheels of the train. In the implementation of the procurement of solid train wheels, PT Kereta Api Indonesia collaborates with several vendors to find the best vendors in the procurement of solid train wheels. The five vendors are PT. IMST, PT. TU, PT. BI, PT. PEI, and PT. IE. In the implementation of the procurement of solid train wheels, there are times when vendors cannot maintain their commitments, which has an impact on ongoing projects. In this study, the author used the Profile Matching Method to determine which vendor has the best rating. Based on the results of research on the five vendors, IMST vendors ranked first with a final result value of 5.71, followed by PEI vendors in second place with a final result value of 5.64, then TU vendors ranked third with a final result value of 5.58, then ranked fourth, namely BI vendors with a final result value of 5.48, and finally ranked fifth, namely IE vendors with a final result value of 4.92. The results of this rating are used as input for the company in determining the main partner and for vendors as an evaluation to improve their performance so that it can become the main choice for the company.